KONSEP EKOLOGIS PADA PERMUKIMAN SUKU LAWALU DI KAMANASA KABUPATEN MALAKA, NUSA TENGGARA TIMUR - Bebhe, Kristiana; Daton, Richardus; Lake, Reginaldo Christophori; Lapenangga, Apridus (Universitas Atma Jaya Yogyakarta, 2019)
Abstract: Kamanasa Village in Malaka Regency is a vernacular village inherited based on the knowledge and local wisdom of the Lawalu tribe. Kamanasa people obey traditions and customs for obedience to tribal ancestors. The concept of obedience arises in settling cultures, in village spatial planning and residential and material use. The architectural concepts that exist in the village of Kamanasa have ecological characteristics in the form, structure and use of materials, also in the behavior of the Kamanasa people. This study focuses on identifying the economic concepts of Kamanasa vernacular architecture and how the sustainability of ecological concepts is maintained. Field observations and literature studies of ecological design principles were used in this study. The results of the study showed that the vernacular village of Kamanasa applied an ecological concept of architecture in accordance with the principles of ecological design that were inherited through the tradition of building houses, linkages with the environment, and social relations in mutual cooperation. The Kamanasa vernacular village is still supported by aspects of traditional beliefs and norms, so the ecological concept of the Kamanasa vernacular architecture deserves to be an ecological concept of cultural architecture.Keywords: Ecological, Vernacular Architecture, Kamanasa VillageAbstrak: Desa Kamanasa di Kabupaten Malaka merupakan desa vernakular yang diwarisi berdasarkan pengetahuan dan kearifan lokal suku Lawalu. Orang Kamanasa taat tradisi dan adat istiadat demi ketaatan terhadap leluhur suku. Konsep ketaatan muncul pada budaya bermukim, pada tata keruangan desa dan rumah tinggal maupun penggunaan material. Konsep berarsitektur yang ada pada desa Kamanasa memiliki ciri-ciri ekologis pada tata bentuk, struktur dan penggunaan material, juga pada perilaku orang Kamanasa. Kajian ini berfokus pada identifikasi konsep eklogis arsitektur vernakular Kamanasa dan bagaimana keberlanjutan konsep ekologis dipertahankan. Observasi lapangan dan kajian pustaka prinsip-prinsip desain yang ekologis digunakan dalam penelitian ini. Hasil penelitian menunjukkan, desa vernakular Kamanasa menerapkan konsep ekologis arsitektur sesuai dengan prinsip-prinsip desain ekologis yang diwariskan melalui tradisi membangun rumah,Â keterkaitan dengan lingkungan, dan hubungan sosial bergotong royong. Desa vernakular Kamanasa masih didukung oleh aspek kepercayaan dan norma-norma adat, sehingga konsep ekologis arsitektur vernakular Kamanasa layak dijadikan konsep arsitektur kiwari yang ekologis.Â Kata kunci: Ekologis, Arsitektur Vernakular, Desa Kamanasa